Dinamika Isu Laut Tiongkok Selatan: Analisis Sumber-Sumber Kebijakan Luar Negeri Tiongkok dalam Sengketa - Arief Bakhtiar Darmawan (Jurnal Ilmiah Hubungan Internasional, 2018)
This article aims to observe the behaviour of China’s foreign policy in the conflict of South China Sea (SCS), by analyzing the internal factors and external factors that affect China’s foreign policy. China is one of the parties that take direct claim on the SCS. China’s claim is overlapping with other parties such as Vietnam, Filipina, Malaysia, dan Brunei. In defending its claims, China seeks to dominate both in the dispute area and in multilateral negotiations. In the dispute area, China seized the area, building land reclamation, and attacked other countries’ ships under various pretexts. In multilateral negotiations, China rejects the intervention of great power countries outside the region and maintains ambiguous and non-binding code of conduct. China also continues to increase its military power to press other countries. The author argues that the internal factors has greater influence on Chinese foreign policy decision and action in the SCS dispute than the external factors. Thus, it could triggers China to keep dominating the issue of SCS disputes.